The Foundations of the Textual Consistency in Surat Al-Iftar - Nahla Hussain Taha (QALAAI ZANIST SCIENTIFIC JOURNAL, 2021)
This study attempts to reveal one of the issues addressed by the linguistics of textual consistency , which in turn is concerned with linguistic mediums (form and signification) that connect the formed elements of the text and contribute to the consistency of its linguistic structure, and is one of the tools of this coherence (textual consistency) that requires the revelation of the synergies and the cohesion between the components of the Qur’anic text in Surat (Al-Iftar) by searching for its formal linguistic tools of (linguistic consistency) which is represented in the element of referral, deletion, substitution and connection, and (lexical consistency). The verbal repetition with diverse relationships of antibiosis, synonyms semi synonyms as the mediums of this consistency